B‐mode and power Doppler ultrasonography of the equine suspensory ligament branches: A descriptive study on 13 horses. Issue 4 (1st March 2018) - Rabba, Silvia; Grulke, Sigrid; Verwilghen, Denis; Evrard, Laurence; Busoni, Valeria
Abstract: Ultrasonography is routinely used to achieve the diagnosis of equine suspensory ligament desmopathy. In human medicine, power Doppler ultrasonography has also been found to be useful for the diagnosis of tendon/ligament injuries. The aim of this prospective, pilot study was to assess the presence or absence of power Doppler signal in suspensory ligament branches and compare B‐mode findings with power Doppler findings in suspensory ligament branches of lame and non‐lame limbs. Thirteen horses were used (eight lame horses, with lameness related to pain in the suspensory ligament branches, and five non‐lame horses). Ten lame limbs and 24 sound limbs were assessed by B‐mode and power Doppler ultrasonography. The severity of power Doppler signal was scored by two independent readers. The B‐mode ultrasonographic examination revealed abnormalities in branches of lame limbs and in branches of sound limbs. Suspensory ligament branches that were considered normal in B‐mode showed no power Doppler signal. However, power Doppler signal was detected in suspensory ligament branches that were abnormal in B‐mode, both in lame and sound limbs. Power Doppler scores were subjectively higher in suspensory ligament branches of lame limbs and in branches with more severe B‐mode changes. Findings supported the use of power Doppler as an adjunctive diagnostic test for lame horses with suspected suspensory desmopathy.